Accounting and Analytical Sources of Economic Risks Identifcation - T. Yu. Serebryakova; O. G. Gordeeva; O. Yu. Kurtayeva (Учёт. Анализ. Аудит, 2018)
The growth of the economy of an enterprise necessitates the use of risk-oriented approach to numerous management systems. Control is no exception. Risk-based control has risk management as a foundation. Risk management means taking risks into account and their analysis. An interesting methodological problem is to research the methodological opportunities to use accounting information in risk management in particular for risk identifcation, assessment and monitoring. The researchers use general scientifc methods of cognition such as systematic approach, logical generalization, legal and linguistic analysis, hypothesis. It is appropriate to identify the risks for all the levels of management and process. The processes at all levels are reﬂected in accounting. The idea is to extract the information necessary for business risk identifcation from the accounting data. The authors propose to use the Yuji Ijiri principle of triple accounting and to extend it to quadruple accounting. The proposed methodology is realized through automated information systems because the necessary detailing could be obtained by using computers. The main idea is that the change in capital is analyzed frst by changes in the balance sheet data and then by revenues and expenses. The results of calculations are presented in formats 1 and 2 accordingly. The results of capital factor analysis of capital due to changes in assets and liabilities are presented in format 3. The inﬂuence of changes of proft components on capital is presented in format 4. The results of the analysis are used to identify and make the primary assessment or risks. The proposed methodology of risk identifcation and their primary assessment makes it possible: 1. To use the data from accounting systems to identify business risks on systematic basis. 2. To ensure the comprehensive approach to risk identifcation. 3. To provide a mental representation of factors inﬂuencing the capital growth.